PRODUCTION AND CONSUMPTION OF CHICKEN EGG IN ONE YEAR PANDEMIC COVID-19 IN CENTRAL LOMBOK : PRODUCTION AND CONSUMPTION OF CHICKEN EGG IN ONE YEAR PANDEMIC COVID-19 IN CENTRAL LOMBOK - Indarsih, Budi; Mohammad Hasil Tamzil; Ni Ketut Dewi Haryani; I Nyoman Sukartha Jaya; Asnawi; Maudina (Universitas Djuanda, 2023)
This study was conducted to determine the level of egg production and consumption of purebred layer chickens for one year of COVID-19 and finding the dominant factors affecting layer chicken production and consumption in Central Lombok. Determination of the sample used purposive sampling method. The data collected in the form of primary data. Primary data were obtained through direct interviews with farmers and consumers using a structured questionnaire and then analyzed using a qualitative descriptive method. The results showed the number of population and egg production in Central Lombok before and after the COVID-19 has sequentially increased by 6.1 % and 5.6 %. Egg production was 49,127 eggs/d during the pandemic, which was previously 46,520 eggs/d. The average family consumption was 3-8 eggs/week, which was higher than the average regional consumption. The COVID-19 pandemic has no effect on production and consumption of chicken eggs. Expensive feed prices are the biggest problem faced by farmers during the COVID-19 pandemic